The changes of intestinal flora and metabolites in atopic dermatitis mice - Wang, Feifei; Wang, Zuding; Qu, Liping (Frontiers in Microbiology, 2024)
IntroductionAtopic dermatitis (AD) is an allergic disease caused by various factors that can affect an individual’s appearance and cause psychological stress. Therefore, it is necessary to investigate the underlying mechanisms and develop effective treatment strategies. The gut microbiota and bacterial metabolism play crucial roles in human diseases. However, their specific role in AD remains unclear.MethodsIn this study, we established a mouse model of AD and found that 2,4-dinitrofluorobenzene disrupted the skin barrier in mice. The species composition of intestinal bacteria was then analyzed by fecal 16s rRNA sequencing. The metabolic level of mice was analyzed by untargeted and targeted metabolomics in stool.ResultsThe levels of filaggrin and aquaporin 3 proteins in the model mice and total superoxide dismutase, catalase and malondialdehyde levels were significantly altered. Additionally, inflammatory factors such as tumor necrosis factor-alpha showed a significant increase. Using 16S rRNA gene sequencing, we identified 270 bacterial species with altered abundances of Ruminococcaceae and Bifidobacteriaceae. The untargeted metabolomic analysis detected 1,299 metabolites. Targeted analysis of free fatty acids revealed 49 metabolites with notable increases in linoleic and linolenic acid levels. Fecal bacterial transplantation experiments have demonstrated that oxidative stress, inflammation, and skin barrier damage were alleviated after transplantation.DiscussionThese findings suggested that the metabolite linoleic acid negatively correlated with Ruminococcaceae and Bifidobacteriaceae may influence AD development. Perturbations in the intestinal bacteria and flora contributed to the development of AD, and the mouse model could serve as a valuable tool for further investigation of therapeutic approaches for managing ADS.